Cardioprotective microRNAs: Lessons from stem cell-derived exosomal microRNAs to treat cardiovascular disease. (June 2019) - Moghaddam, Abbas Shapouri; Afshari, Jalil Tavakol; Esmaeili, Seyed-Alireza; Saburi, Ehsan; Joneidi, Zeinab; Momtazi-Borojeni, Amir Abbas
Abstract: The stem cell-based therapy has emerged as a promising therapeutic strategy for treating cardiovascular ischemic diseases (CVIDs), such as myocardial infarction (MI). However, some important functional shortcomings of stem cell transplantation, such as immune rejection, tumorigenicity and infusional toxicity, have overshadowed stem cell therapy in the setting of cardiovascular diseases (CVDs). Accumulating evidence suggests that the therapeutic effects of transplanted stem cells are predominately mediated by secreting paracrine factors, importantly, microRNAs (miRs) present in the secreted exosomes. Therefore, novel cell-free therapy based on the stem cell-secreted exosomal miRs can be considered as a safe and effective alternative tool to stem cell therapy for the treatment of CVDs. Stem cell-derived miRs have recently been found to transfer, via exosomes, from a transplanted stem cell into a recipient cardiac cell, where they regulate various cellular process, such as proliferation, apoptosis, stress responses, as well as differentiation and angiogenesis. The present review aimed to summarize cardioprotective exosomal miRs secreted by transplanted stem cells from various sources, including embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs), mesenchymal stem cells (MSCs), and cardiac stem/progenitor cells, which showed beneficial modulatory effects on the myocardial infracted heart. In summary, stem cell-exosomal miRs, including miR-19a, mirR-21, miR-21-5p, miR-21-a5p, miR-22 miR-24, miR-26a, miR-29, miR-125b-5p, miR-126, miR-201, miR-210, and miR-294, have been shown to have cardioprotective effects by enhancing cardiomyocyte survival and function and attenuating cardiac fibrosis. Additionally, MCS-exosomal miRs, including miR-126, miR-210, miR-21, miR-23a-3p and miR-130a-3p, are found to exert cardioprotective effects through induction of angiogenesis in ischemic heart after MI. Graphical abstract: Image 1 Highlights: MSC-derived exosomal miRs can reduce infarct size and improve cardiac survival and function after heart failure. MSC-derived exosomal miRs exert cardioprotective effects through induction of angiogenesis in ischemic heart after MI. CPC-derived exosomal miRs show therapeutic potential for mitral regurgitation, atrial enlargement, and heart failure.